Roman stonemasonry workshops in the Ig area - Lozić, Edisa (Arheološki vestnik, 2009)
This article presents a hypothesis about three Roman period stonemasonr y workshops that operated in the area of Strahomer, Iška vas, and Ig, all of them located on the southern edge of the Ljubljansko barje, to the south of the Roman Emona. The hypothesis is based on the formal analysis of the grave stelae as well as their spatial distribution